Stimulus to rooting of Saccharum sp. mini-cuttings with talc indole-butyric acid (Research, Society and Development, 2021)
Sugarcane is a commercially important species for sugar and biofuel production and because of the high demand for plant material in planting, new means of propagation are being developed and require improvements. Therefore, the objective of this study was to evaluate the effect of different concentrations of indole-butyric acid (IBA) applied in the form of talc on the initial growth and emergence of sugarcane mini-cuttings used for the system of pre-sprouted plantlets (PSP). Mini-cuttings were treated with concentrations of 0, 500, 1000, 1500 and 2000 mg kg-1 of IBA in the form of talc and evaluated for emergence and initial growth. There was no difference between IBA concentrations for the physiological, biometric and dry mass variables analyzed. The sugarcane plantlets formed had emergence above 89%, functional photosynthetic apparatus, 4.4 leaves on average, stem diameter of 11.90 mm, shoot length of 12.18 cm, leaf area of 108.81 cm² and root area of 142.17 cm². Shoot dry mass and root dry mass were equal to 2.27 and 1.20 grams, respectively. Thus, concentrations of up to 2000 mg kg-1 of IBA applied in the form of talc in sugarcane mini-cuttings had no effect on rooting and initial growth of plantlets.